2001
DOI: 10.1074/jbc.m008598200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Thymine to 5-Formyluracil in DNA Promotes Misincorporation of dGMP and Subsequent Elongation of a Mismatched Primer Terminus by DNA Polymerase

Abstract: 5-Formyluracil (fU) is a major oxidative thymine lesion generated by ionizing radiation and reactive oxygen species. In the present study, we have assessed the influence of fU on DNA replication to elucidate its genotoxic potential. Oligonucleotide templates containing fU at defined sites were replicated in vitro by Escherichia coli DNA polymerase I Klenow fragment deficient in 3-5-exonuclease. Gel electrophoretic analysis of the reaction products showed that fU constituted very weak replication blocks to DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…Hela-S3 cells were from the National Cell Culture Center (Minneapolis, MN). [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 , 2′-D]-5-formyl-2′-deoxyuridine was prepared according to previously described procedures 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Hela-S3 cells were from the National Cell Culture Center (Minneapolis, MN). [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] N 2 , 2′-D]-5-formyl-2′-deoxyuridine was prepared according to previously described procedures 8 .…”
Section: Methodsmentioning
confidence: 99%
“…[5] DNA polymerization across fo Ura in vitro with the E. coli Pol I Klenow fragment introduces guanine (Gua) as well as adenine (Ade) in DNA. [6] Zhang et al reported that dCTP as well as dATP are frequently incorporated but only a small amount of dGTP is incorporated into the site opposite to fo Ura in DNA by the Klenow fragment (exo-). [7] These misincorporations induce mutation (from A:T to G:C and A:T to C:G) by mispairing between an ionized form of fo Ura and Gua or between fo Ura and Cyt during DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…30UR containing a urea residue was prepared by mild alkaline treatment of 30TG5R and 30TG5S (18,41). 25FU, 25HMU, and 25OG containing 5-formyluracil (fU), 5-hydroxymethyluracil (hmU), and 7,8-dihydro-8-oxoguanine (8-oxoG), respectively, were chemically synthesized (42)(43)(44). 25HOU, 25HOC, 34FP, and 25OXA containing 5-hydroxyuracil (hoU), 5-hydroxycytosine (hoC), 2,6-diamino-4-hydroxy-5-N-methylformamidopyrimidine (mFapyG), and oxanine (Oxa), respectively, were prepared by DNA polymerase reactions with modified 2Ј-deoxynucleoside 5Ј-triphosphates as reported previously (19,(43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%